2019
DOI: 10.1002/tox.22746
|View full text |Cite
|
Sign up to set email alerts
|

Epimagnolin A inhibits IL‐6 production by inhibiting p38/NF‐κB and AP‐1 signaling pathways in PMA‐stimulated THP‐1 cells

Abstract: Epimagnolin A is a lignan obtained from the flower buds of Magnolia fargesii, which is traditionally used in Asian medicine for treating headache and nasal congestion. A herbal compound fargesin obtained from M. fargesii, has exerted anti‐inflammatory effects in human monocytic THP‐1 cells in the previous study. The anti‐inflammatory effects of epimagnolin A, however, have been not elucidated yet. In this study, it was demonstrated that epimagnolin A reduced phorbol‐12‐myristate‐13‐acetate (PMA)‐induced IL‐6 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Fargesin is one of the main components of Magnolia fargesii and has traditionally been used to treat sinusitis and inflammation. Moreover, fargesin's anti-inflammatory effects can inhibit NF-ĸB signaling and reduce nitric oxide in a variety of cell types [25][26][27]. A recent study has shown that fargesin can inhibit murine malignancy by regulating the P38/MAPK signaling pathway [28].…”
Section: Introductionmentioning
confidence: 99%
“…Fargesin is one of the main components of Magnolia fargesii and has traditionally been used to treat sinusitis and inflammation. Moreover, fargesin's anti-inflammatory effects can inhibit NF-ĸB signaling and reduce nitric oxide in a variety of cell types [25][26][27]. A recent study has shown that fargesin can inhibit murine malignancy by regulating the P38/MAPK signaling pathway [28].…”
Section: Introductionmentioning
confidence: 99%
“…The liver function has been improved by inhibiting NF-κB induced-activation of proinflammatory factors such as tumor necrosis factor-alpha (TNFα), interleukin-6 (IL-6), and PGE2, and iNOS, COX-2, and matrix metallopeptidase-9 in LPSstimulated RAW 264.7 macrophages as well as in acute liver fibrosis mouse model [38,40,41]. Lignan can inhibit binding affinity between NF-κB and AP-1 transcription factors to interleukins (IL-6 promoter and IL-6) production through p38/NF-κB and AP-1 signaling pathways in cancer [42]. It has been reported that LBDE repressed the activation of COX-2 and iNOS genes by blocking the activation of NF-κB [12,15,23].…”
Section: Discussionmentioning
confidence: 99%
“…After 2 h of PSO pretreatment, JME/CF15 cells were stimulated with 10 ng/ml IL-13 for 24 h at 37˚C to generate a cell-based AR model. In this paper, cells were pretreated with 10 nM PMA for 24 h and 15 µl SP600125 for 24 h at 37˚C, as outlined in previous studies (22,23) Database. According to the GEO (https://www.ncbi.nlm.nih.…”
Section: Methodsmentioning
confidence: 99%